Variability of the Turkana low‐level jet in reanalysis and models: implications for rainfall - King, JA; Engelstaedter, S; Washington, R; Munday, C (American Geophysical Union, 2021)
The complex topography of East Africa poses challenges for accurate modelling of regional climate. The Turkana Channel in northwestern Kenya is an important feature because of a persistent low‐level jet (LLJ) which blows through it, which has complex interactions with local and regional rainfall. We establish the annual cycle and interannual variability of the LLJ in the ERA5, MERRA‐2, and JRA‐55 reanalyses. The jet is strongest during wet seasons in the surrounding region. Results suggest a statistically significant weakening of the LLJ over the last 30‐40 years in two out of the three reanalyses. We propose an explanation based on the jet's relationship with regional warming patterns and zonal surface pressure gradients, which link the jet to larger‐scale climate dynamics including the Walker Circulation. If these changes continue in future, there may be significant implications for rainfall including increases in northwest Kenya and decreases further inland. However, the global models used to produce climate projections vary in their simulations of the LLJ in part because of their representations of topography. Consequently, it is not possible to assess how future LLJ changes will affect regional climate using CMIP5 models alone. Differences between the reanalyses preclude their direct use for model evaluation. Improving the processes by which topographical observations are mapped onto model grids could lead to improvements in simulation of East African climate. A field campaign to measure the LLJ directly could resolve uncertainties in the literature, help constrain reanalyses, and determine which models have the most realistic LLJ representation.